Typology and Effects of Co‐opetition in Buyer–Supplier Relationships: Evidence from the Chinese Home Appliance Industry. 供应链关系中竞合分类及其影响：来自中国家电业的实证研究. (November 2014) - Liu, Yi; Luo, Yadong; Yang, Pianpian; Maksimov, Vladislav
Abstract Building on the co‐opetition perspective, this study takes a unified approach to examine relationship benefits and transaction costs in buyer–supplier relationships. We argue that buyer–supplier vertical dyads fall into one of four distinct co‐opetition types based on their respective degrees of cooperation and competition. Each co‐opetition situation then corresponds to unique levels of relationship benefits and transaction costs. A sample of 225 supplier–buyer dyads from the Chinese home appliance industry confirms that competition has a positive effect on transaction costs and a negative effect on relationship benefits, while cooperation stimulates greater relationship benefits but affects transaction costs mainly at low competition levels. The results advance prior research on buyer–supplier relationships and co‐opetition and offer valuable avenues for future research.